Characteristics and Outcomes of Patients With Advanced Chronic Systolic Heart Failure Receiving Care at the Veterans Affairs Versus Other Hospitals. (January 2015) - Jones, Linda G.; Sin, Mo-Kyung; Hage, Fadi G.; Kheirbek, Raya E.; Morgan, Charity J.; Zile, Michael R.; Wu, Wen-Chih; Deedwania, Prakash; Fonarow, Gregg C.; Aronow, Wilbert S.; Prabhu, Sumanth D.; Fletcher, Ross D.; et al.
<x xml:space="preserve">Abstract</x> Background— Characteristics and outcomes of patients with heart failure and reduced ejection fraction receiving care at Veterans Affairs (VA) versus non-VA hospitals have not been previously reported. Methods and Results— In the randomized controlled Beta-blocker Evaluation of Survival Trial (BEST; 1995-1999), of the 2707 (bucindolol=1353; placebo=1354) patients with heart failure and left ventricular ejection fraction ⩽35%, 918 received care at VA hospitals, of which 98% (n=898) were male. Of the 1789 receiving care at non-VA hospitals, 68% (n=1216) were male. Our analyses were restricted to these 2114 male patients. VA patients were older with higher symptom and comorbidity burdens. There was no significant between-group difference in unadjusted primary end point of 2-year all-cause mortality (35% VA versus 32% non-VA; hazard ratio associated with VA hospitals, 1.09; 95% confidence interval, 0.94–1.26), which remained unchanged after adjustment for age and race (hazard ratio, 1.00; 95% confidence interval, 0.86–1.16) or multivariable adjustment, including cardiovascular morbidities (hazard ratio, 0.94; 95% confidence interval, 0.80–1.10). There was no between-group difference in cause-specific mortalities or hospitalizations. Chronic kidney disease, pulmonary edema, left ventricular ejection fraction <20%, and peripheral arterial disease were significant predictors of mortality for both groups. African America race, New York Heart Association class IV symptoms, atrial fibrillation, and right ventricular ejection fraction <20% were associated with higher mortality among non-VA hospital patients only; however, these differences from VA patients were not significant. Conclusions— Patients with heart failure and reduced ejection fraction receiving care at VA hospitals were older and sicker; yet their risk of mortality and hospitalization was similar to younger and healthier patients receiving care at non-VA hospitals. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00000560.